2005
DOI: 10.1016/s0002-9440(10)62052-4
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Antigenic Drive and Tumor-Infiltrating Accessory Cells in the Pathogenesis of Helicobacter-Induced Mucosa-Associated Lymphoid Tissue Lymphoma

Abstract: Gastric B-cell lymphoma of mucosa-associated lymphoid tissue type is closely linked to chronic Helicobacter pylori infection. Most clinical and histopathological features of the tumor can be reproduced by prolonged Helicobacter infection of BALB/c mice. In this study, we have addressed the role of antigenic stimulation in the pathogenesis of the lymphoma by experimental infection with Helicobacter felis, followed by antibiotic eradication therapy and subsequent re-infection. Antimicrobial therapy was successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
59
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 49 publications
6
59
1
Order By: Relevance
“…[174][175][176][177] Oral infection of A/J mice with Helicobacter sp leads to development of hepatic inflammatory lesions containing HEVs, the production of CCL21 and CXCL13 and influx of B and T cells. 177 Infection of BALB/c mice with Helicobacter felis resulted in a massive influx of B cells and lymphoorganogenesis in the stomach.…”
Section: Mouse Models Of Marginal Zone B-cell Lymphomamentioning
confidence: 99%
See 3 more Smart Citations
“…[174][175][176][177] Oral infection of A/J mice with Helicobacter sp leads to development of hepatic inflammatory lesions containing HEVs, the production of CCL21 and CXCL13 and influx of B and T cells. 177 Infection of BALB/c mice with Helicobacter felis resulted in a massive influx of B cells and lymphoorganogenesis in the stomach.…”
Section: Mouse Models Of Marginal Zone B-cell Lymphomamentioning
confidence: 99%
“…177 Infection of BALB/c mice with Helicobacter felis resulted in a massive influx of B cells and lymphoorganogenesis in the stomach. 174,175 It was reported that after 23 months of infection, 25-75% of these mice developed low-or intermediate-grade MZBCLs. In these mice, regression of the infiltrates after anti-bacterial therapy was also demonstrated.…”
Section: Mouse Models Of Marginal Zone B-cell Lymphomamentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have implicated the abundant population of tumor-infiltrating T cells in providing growth signals to tumor B cells. [10][11][12] In one study, depletion of T cells was shown to abrogate the proliferation of explanted MALT lymphoma cultures. 12 We and others have reported that MALT lymphomas express high levels of interleukin-4 (IL-4) and other T helper 2 cytokines in vivo, supporting a role for T helper 2-polarized T-helper responses in early MALT lymphomagenesis.…”
mentioning
confidence: 99%